Efektivitas Penggunaan Bukti Digital dalam Pembuktian Perkara Perdata: Analisis terhadap Integrasi Electronic Evidence dalam Hukum Acara Perdata Nasional - Ramadani, Nurmagrifah; Haidar, Muhammad; Setiono, Aulia Putri (Universitas Sains dan Teknologi Komputer, 2025)
The increasing integration of digital evidence into civil litigation processes in Indonesia reflects a significant shift towards modernization of the judicial system. This study examines the effectiveness of digital evidence in civil case proceedings by analyzing court decisions, conducting expert interviews, and reviewing applicable regulations. The findings reveal that while digital evidence is increasingly accepted, challenges remain regarding authentication, technical capacity of legal practitioners, and the absence of standardized procedures. Regulatory advancements such as the enactment of Law Number 11 of 2008 on Electronic Information and Transactions (ITE Law) and Supreme Court Regulation Number 1 of 2019 have bolstered the legal recognition of digital evidence. However, inconsistent application and limited forensic capabilities hinder optimal utilization. This research contributes to the discourse by emphasizing the need for capacity building, procedural standardization, and a more robust technological infrastructure within the judicial framework. Future studies are encouraged to adopt broader and comparative approaches to strengthen digital evidence practices in civil litigation.